The Influence of Social Media Advertising on Guest Decisions: Case Study from Hotels in Gunungsitoli City, Indonesia - Telaumbanua, Abdinius; Bate’e, Maria Magdalena; Zebua, Emanuel; Laia, Otanius (Golden Ratio of Data in Summary, 2025)
Currently, advertising development is progressing very rapidly. The progress in advertising development is accompanied by increasingly tight competition between producers of goods or services who use advertising services to inform about the products or services they produce. Advertising is a special form of communication that fulfills marketing functions. Social media is a means that allows users to present themselves or communicate with various texts, images, videos, and form social bonds virtually. This research aims to discover how social media advertising influences guests' decisions when choosing a hotel in Gunungsitoli. The research method used is quantitative with a survey approach; researchers also use questionnaires in data collection. Researchers tested the hypothesis using multiple regression analysis techniques, and the calculations were assisted by utilizing the software program SPSS (Statistical Program for Social Science) version 26. This research found that the social media advertising variable (X) hypothesis was accepted and partially positively and significantly influenced guest decisions. (Y) Choose a hotel in the city of Gunungsitoli. Then this research also found that Media Advertising (X) had an influence of 0.500 or 50% on the guest's decision to choose a hotel in the city of Gunungsitoli. Meanwhile, the other 50% is influenced by different factors.